PENINGKATAN PEMAHAMAN KONSEP GERAK MENGGUNAKAN MEDIA CD DENGAN PENDEKATAN KONSTRUKTIVISTIK KELAS VII B SEMESTER 2 SMP KESATRIAN 1 SEMARANG TAHUN AJARAN 2009/2010 - Latifah Syayidah (Universitas PGRI Semarang, 2010)
The action research classes entitle ?óÔé¼?ôImprovement move conceptcomprehension using CD as media with constrictive approach class VIIB semester 2 SMP Kesatrian 1 Semarang in academic year 2009/2010?óÔé¼?Ø.The problems in this action research was how to improvement moveconcept comprehension using CD as media learning with constructiveapproach students class VII B in SMP Kesatrian 1 Semarang.?Thisresearch has purpose to know is there improvement move conceptcomprehension using CD as media with constructive approach thestudents class VII B in SMP Kesatrian 1 Semarang. Subject of thisresearch was students class VII B. The factors that researched in thisresearch was factor of students, it was result study of the students insubject IPA. The factor from the teacher , include preparation andcarrying out of learning process. Method of collecting data that used inthis research was observation and test methods. Test method that used isessay test method.The result of the first sickles evaluation learningmethod application using constructive approach could improving abilityconcept comprehension especially students class VII B semester 2 SMPKesatrian 1 Semarang in academic year 2009/010. This matter seen inpercentage classical study completeness from the first sickles 70.21%with average 67.87% has improvement in the second sickles 87.23%with average 72.76. The improve quality of the teacher ability inlearning IPA with percentage in the first sickles has average 85% hasimprove in the second sickles 90%. Based on this the action research,suggestion that submitted was following: 1) the teacher must applied CDas media with constructive approach because it could improved abilityof the students in finished main item move discussion, 2) constructiveapproach with CD as media must be socialization to the teacher ofsubject IPA in order that applied in learning class, 3) the headmastergive motivation and facility in order that the teacher of subject IPAusing learning innovative model to overcome the problem for thestudents.Key words: konstruktivistik, pemahaman konsep, gerak